CENTRAL INLAND FISHERIES RESEARCH STATION, CALCUTTA—ANNUAL REPORT FOR THE YEAR 1953 - Mandapam, CMFRS (Indian Journal of Fisheries, 2016)
During the year under review, the headquarters of this ResearchStation was shifted from Barrackpore to Calcutta as a temporary measuretill such time as the proposed laboratory and hostel buildings at Barrackporeare constructed. The Riverine and Lacustrine Section was shifted toAllahabad. The Motor Launch Bhetki was used for fishery investigationsin the estuarine areas. The year under report registered substantial progressin the programmes of work, both in the field and in the laboratory.